Greenmail and tunneling: between ethics and economic growth (2019)
Greenmail is used by some employers or brokers to make transfers that wouldbenefit the shareholders of the organizations, which is used as a data acquisitionstrategy with the aim of increasing the company´s assets and gain benefits.On the other hand, companies issuing shares and by allowing other firms to havepart of the assets of the organization, pyramids or tunnelings are formed whichbenefit the major shareholders, taking decisions in which do not allow todistribute the profits among all shareholders and benefiting only those with thepreferred shares.Therefore, if Colombian companies use these two cuestioned practices for itsethic, as strategies for decision making, less effort by the executives will be allow,more effective results will be obtained to enhance the assets, but at the expense ofmorality.